A split-face comparison of low-fluence Q-switched Nd: YAG laser plus 1550 nm fractional photothermolysis vs. Q-switched Nd: YAG monotherapy for facial melasma in Asian skin. (June 2013) - Kim, Hei Sung; Kim, Eun Kyung; Jung, Kyoung Eun; Park, Young Min; Kim, Hyung Ok; Lee, Jun Young
Abstract Background: Melasma is a common pigmentary disorder which poses substantial therapeutic challenge. Combined therapy may be beneficial in Asians, where mixed type melasma is dominant. Objective: We sought to assess the efficacy and safety of a 1064 nm Q-switched Nd: YAG (1064 QSNY) and a nonablative 1550 nm erbium-doped fractional photothermolysis (NFP) treatment in Asian melasma. Methods: This was a split face study, in which 26 patients were treated with the 1064 QSNY (6 mm spot size, 1.2–1.4 J/cm2 fluence) for 10 sessions at 2-week intervals to the entire face, and with the NFP (dynamic mode, pulse energy 6–8 mJ/microthermal zone (MTZ); total density 300 MTZs/cm2) for five sessions at 4-week intervals to the experimental side of the face. Efficacy variables were modified Melasma Area and Severity Index (mMASI), the physician's global assessment (PhGA), and patient's subjective global assessment (PGA). Safety was evaluated through the reporting of adverse events. Results: The percentage of subjective improvement was virtually identical on both sides. The mMASI corroborated the patients' subjective estimate, both in terms of the degree of improvement and the lack of difference between the 1064 QSNY + NFP and the 1064 QSNY treated sides. No serious side effects were reported in either side. Conclusions: Our findings do not support the hypothesis of NFP providing a substantial benefit in treating the melasma when compared with the lone treatment of the 1064 QSNY.